Primary Non-Hodgkin Lymphoma in the Maxillary Vestibule: Report of a Rare Case - SeyedOmid Mahdavi; Najmehsadat Boostani; Neda Gholami; Atessa Pakfatrat; Nasrollah Saghravanian (Mashhad University of Medical Sciences, 2012)
Introduction: Lymphoma is the malignant neoplasm of lymphocytes which is divided into 2 categories: Hodgkin and Non- Hodgkin lymphoma (NHL). The occurrence of primary lymphoma in oral cavity is uncommon and comprises only 2% of all extra-nodal lymphomas. The aim of this study was introduction of a case of NHL in oral cavity, presenting the related signs and its differentiation from similar lesions.Case report: A 72 year old man referred with complaint of a swelling in left side of the face and demanding to extract the loosen tooth. The swelling had been present for one year accompanying pain and the lesion had been treated as a dental infection. The pain had subsided but swelling had slow growing after medical treatment. Intraoral examination, revealed a swelling with rubbery consistency in depth of left maxillary vestibule extending to the tuberosity. Second premolar tooth was loosen (third degree). In panoramic view, there was an ill-defined radiolucency from mesial of second premolar to distal of alveolar ridge. This tooth had floating in air view. Incisional biopsy was made under the diagnosis of salivary or mesenchymal tumor. According to histopathology and immunohistochemistry reports, lesion was diagnosed as a diffuse large B-cell lymphoma. The patient was referred to oncologist for treatment.Conclusion: As some of the signs and symptoms of oral lymphoma may be mistaken with dental infections, it is important for a dentist to detect its signs and symptoms and make in time referral.